Asian leadership in policy and governance - Berman, Evan; Haque, M. Shamsul (Emerald Group Publishing Limited, 2015)
Asian Leadership in Policy and Governance examines contemporary challenges facing public leaders in Asia, providing insight into leadership processes and contexts past practices affecting effective governance and policy leadership. The book provides a broad range of insightful and detailed cases of international and domestic interest in East and Southeast Asia, and is relevant to all disciplines concerned with politics, public governance and public affairs. The cases cover such topics as regional development and integration, transnational migration, and domestic topics of economic, political and educational development. The volume is informed by modern notions of leadership which include governance in a polycentric world (including civil society), the rise of a new generation, regionally and globally connected problems, expectations for increased integrity, transparency and effectiveness from its leaders, and enduring expectations that leaders and nations meet their populace's needs for health, prosperity and security. Such a focus on Asian leadership in modern context makes this book timely and interesting.
Keywords: Political leadership -- Asia.; Political planning -- Asia.; Asia -- Politics and government.; Asia.; elektronické knihy; electronic books